2016
DOI: 10.3389/fmicb.2016.01324
|View full text |Cite
|
Sign up to set email alerts
|

The Aspergillus flavus Histone Acetyltransferase AflGcnE Regulates Morphogenesis, Aflatoxin Biosynthesis, and Pathogenicity

Abstract: Histone acetyltransferases (HATs) help regulate fungal development and the production of secondary metabolites. In this study, we determined that the HAT AflGcnE influenced morphogenesis and aflatoxin biosynthesis in Aspergillus flavus. We observed that AflGcnE localized to the nucleus and cytoplasm during the conidial production and germination stages, while it was located mainly in the nucleus during the hyphal development stage. Deletion of AflgcnE inhibited the growth of A. flavus and decreased the hydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
92
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 60 publications
3
92
0
Order By: Relevance
“…Aspergillus flavus produces sclerotia as a structural barrier again its harsh surroundings (Lan et al ., ). After growth on sclerotial‐inducing Wickerham medium (WKM) at 37°C for 7 days, 75% ethanol was used to wash off the aerial hyphae of each strain, and the results showed that the number of sclerotial was significantly decreased in the Δ aflO mutant when compared with the WT and Δ aflO‐C strains (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Aspergillus flavus produces sclerotia as a structural barrier again its harsh surroundings (Lan et al ., ). After growth on sclerotial‐inducing Wickerham medium (WKM) at 37°C for 7 days, 75% ethanol was used to wash off the aerial hyphae of each strain, and the results showed that the number of sclerotial was significantly decreased in the Δ aflO mutant when compared with the WT and Δ aflO‐C strains (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Reproduction is an important event for fungal life cycles, thus, A. flavus produces more conidia in suitable conditions, but generates more sclerotia in harsh environments (Horowitz Brown et al ., ), which is considered a sex‐based adaptation to adapt adverse environment (Lan et al ., ). Interestingly, no studies on homologues of AflO in relation to the regulation of development in fungi have been performed, and one possible reason is that AflO has generally been studied as an aflatoxin cluster gene.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our experimental data reveal a localization of Gcn5 in the nucleus and cytoplasm of B. bassiana hyphal cells as previously observed in A. flavus (Lan et al ., ). This subcellular localization is somewhat different from the localization of C. albicans Gcn5 in the nucleus at stationary phase but in the cytoplasm during vegetative growth in a morpha‐independent fashion (Chang et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the absence of gcn5 in B. bassiana led to a complete loss of virulence through the normal cuticle infection and a great delay in lethal action through the cuticle‐bypassing infection, highlighting an indispensability of Gcn5‐governed H3 acetylation and gene activity for the fungal virulence to the susceptible model insect. This is well in accordance with the loss of virulence or pathogenicity in the Δ gcn5 mutants of A. flavus (Lan et al ., ), C. neoformans (O'Meara et al ., ) and U. maydis (González‐Prieto et al ., ). Our data also unveil a vital role for Gcn5 in not only the biosynthesis and secretion of extracellular enzymes and Pr1 proteases presumably involved in the cuticle penetration crucial for the normal infection but also the dimorphic transition, which is essential for the rapid proliferation of fungal cells in insect haemocoel and hence determinant to the speed of host mummification to death (Wang et al ., 2016; Zhu et al ., ; Chu et al ., ; Zhang et al ., ).…”
Section: Discussionmentioning
confidence: 99%